1992
DOI: 10.1038/359082a0
|View full text |Cite
|
Sign up to set email alerts
|

Virulent strains of Toxoplasma gondii comprise a single clonal lineage

Abstract: The protozoan Toxoplasma gondii is a prevalent parasite in wild and domestic animals worldwide, being transmitted through the food chain by carnivorous feeding and scavenging. Toxoplasma normally divides asexually to yield a haploid form that can infect virtually any vertebrate but it also has a well defined sexual cycle that occurs exclusively in cats. Toxoplasma has become important as an often fatal opportunistic pathogen in patients with AIDS, although the 15-85% of adult human populations that are chronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
455
3
17

Year Published

1994
1994
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 684 publications
(485 citation statements)
references
References 20 publications
10
455
3
17
Order By: Relevance
“…Multilocus and multi-chromosome genotyping of isolates from South America, Asia and Africa with PCR-RFLP or microsatellite markers revealed that the majority of them possess type I, II or III alleles (mainly I and III), identical to those found in the three major lineages, but these have segregated differently among the loci analyzed. These isolates, presenting different mixtures of classical alleles can be considered as T he first genotyping studies on Toxoplasma gondii strains, performed on a limited number of laboratory strains and isolates mainly from France or from USA, lead to the description of a clonal population structure with three main lineages, designated as type I, II and III, related to mouse-virulence (Dardé et al, 1988(Dardé et al, , 1992Sibley & Boothroyd, 1992;Howe & Sibley, 1995). But genotypes not belonging to the three main lineages were found predominant in other continents where the population structure of Toxoplasma was more complex, with a higher genetic diversity than initially described.…”
Section: Toxoplasma Genotypes the Three Main Clonal Lineagesmentioning
confidence: 99%
“…Multilocus and multi-chromosome genotyping of isolates from South America, Asia and Africa with PCR-RFLP or microsatellite markers revealed that the majority of them possess type I, II or III alleles (mainly I and III), identical to those found in the three major lineages, but these have segregated differently among the loci analyzed. These isolates, presenting different mixtures of classical alleles can be considered as T he first genotyping studies on Toxoplasma gondii strains, performed on a limited number of laboratory strains and isolates mainly from France or from USA, lead to the description of a clonal population structure with three main lineages, designated as type I, II and III, related to mouse-virulence (Dardé et al, 1988(Dardé et al, , 1992Sibley & Boothroyd, 1992;Howe & Sibley, 1995). But genotypes not belonging to the three main lineages were found predominant in other continents where the population structure of Toxoplasma was more complex, with a higher genetic diversity than initially described.…”
Section: Toxoplasma Genotypes the Three Main Clonal Lineagesmentioning
confidence: 99%
“…Several recent studies have taken advantage of these tools and the highly clonal population structure of Toxoplasma [30], to map genes in the parasite that control important phenotypic differences between parasite lineages. These studies have lead to the important discovery that ROP proteins play vital roles in modulating host cell signaling and parasite virulence.…”
Section: Pin-pointing Effectors Of Virulencementioning
confidence: 99%
“…For 850, primers were: 5'-AAGGACCTGGTAACAGTCC-3' and 5'-TCAAG-GCTTGGATGTTTCG-3 '. The conditions of PCR referred to by Sibley & Boothroyd (1992), were optimised to: 40 cycles of 94° C for 1 min. 50° C for 2 min, and 72° C for 2 min.…”
Section: Rflp Analysesmentioning
confidence: 99%
“…The virulence of the strains is usually determined on the basis of lethal dose of tachyzoites (Cruz, 1989). On the basis of lethal doses and tachyzoite virulence for mice different strains of T. gondii were divided into two groups: virulent strains (LD100< 10 tachyzoites), which are able to cause acute lethal infection with ascites in mice, and avirulent strains (LD100 > 10 3 ), which cause chronic infection typical by the formation of tissue cysts in the brain of mice (Sibley & Boothroyd, 1992). Ferreira et al (2001) divided T. gondii isolates into three groups according to mortality and period of survival in mice infected with the dose of ten tachyzoites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation